Map locations of mouse hepatitis virus temperature-sensitive mutants: confirmation of variable rates of recombination. - Fu, K (1994)
Using standard genetic recombination techniques, studies in our laboratory suggest that recombination rates are very high and vary in different portions of the mouse hepatitis virus (MHV) genome. To determine the actual recombination frequencies in the MHV genome and localize the nucleotide boundaries of individual viral genes, we have sequenced temperature-sensitive and revertant viruses to identify the location of specific mutant alleles. Complementation group F RNA+ ts mutants (LA7, NC6, and NC16) each contained a unique mutation which was tightly linked to the ts phenotype and resulted in a conservative or nonconservative amino acid change in the MHV S glycoprotein gene. In agreement with previous recombination mapping studies, the mutation in LA7 and NC6 mapped within the S1 domain while NC16 mapped within the S2 domain. To determine the map coordinates of the MHV polymerase genes, several RNA- mutants and their revertants belonging to complementation groups C (NC3 and LA9) and E (LA18 and NC4) were also sequenced. Mutations were identified in each virus that were tightly linked to the ts phenotype and resulted in either a conservative or nonconservative amino acid change. The group C allele spanned the ORF 1a/ORF 1b junction, while the group E mutants mapped at the C terminus of ORF 1b about 20 to 22 kb from the 5' end of the genome. Mutation rates, calculated from the reversion frequencies of plaque-purified ts viruses requiring a single nucleotide alteration for reversion, approached 1.32 (+/- 0.89) x 10(-4) substitutions per nucleotide site per round of template copying. Detailed recombination mapping studies across known distances between these different ts alleles has confirmed that homologous recombination rates approached 25% and varied within different portions of the MHV genome.